Neither prepared nor transformed: Institutional responses to unconventional oil and gas development in Australian and Canadian communities. (August 2022) - Markey, Sean; Halseth, Greg; Ryser, Laura; Argent, Neil; Haslam-McKenzie, Fiona
Abstract: Resource dependent regions in Australia, Canada, and in other industrialized areas have experienced rapid change due to forces of both political and economic restructuring over the past three decades. Policy and program responses by senior levels of government to these accelerating processes of change have too often only exacerbated the negative impacts of major resource exploitation. As a result, rural and small-town places dependent upon primary industries and natural resource sectors continue to struggle to find traction in a new economy marked by the vagaries of demographic, economic, social, cultural, political, and environmental change. In this paper, we explore these resource economy and institutional dynamics within the context of unconventional oil and gas development (UOGD). Our comparative case context includes the Surat Basin in eastern Australia and the Peace River region in northeastern British Columbia, Canada. Both regions have significant recent experience with UOGD. The paper draws upon staples theory and evolutionary economic geography to frame the dynamics of truncated development patterns and the prospects for path variation. Despite the well-known negative impacts and disruptions associated with major resource projects, we make three inter-related arguments challenging the efficacy of senior government responses to the community and regional impacts of UOGD. These are that senior governments: 1) react too slowly in their mitigation responses; 2) are generally dragged into action by local opposition to construct institutional and redistributive funding measures to compensate for local disruption, that; 3) ultimately fall short in terms of offering any kind of strategic, post-resource boom transformational potential to restore or redirect the economic future of resource regions.